PERENCANAAN SUMBER DAYA APARATUR DALAM RANGKA MENYONGSONG KEBIJAKAN PRA-DEKONSENTRASI ADMINISTRASI DI TIGA MUNICIPIO DI TIMOR LESTE - Constantino Exposto; Sarwono .; Lely Indah Mindarti (Universitas Tribhuwana Tunggadewi, 2015)
Planning of human resources as a key instrument in the implementation of delegation authority or sharing of power to the three Municipio through Law No. 4/2014 on the organic statute of structure administrative pre-deconcentration in East Timor legally, planned, gradual and continued in three Municipio. The results showed that technically the human resources planing in terms of quality and quantity is not enough to fill a administrative pre-deconcentration in three Municipio. While planning the placement of employees on the structure of the administrative pre-concentration has not done. Because it is the competence of National Permanent Technique Group which consists of 12 Ministers, four secretary of state and civil service commission. supporting factors, among others: the strategic plan, (Municipality Strategic Development MSD), budgeting, the new activities and design of structure and official duties. The inhibitory is the economic situation, politics, social and culture, legislation, technology and competitors. Advices research, Pertaining to the human resource, relating to the planning of personnel resources is need further research studies related gender, As in the process of administrative pre-deconcentration Municipio is a new concept and the first time implemented in three Municipio in East timor. The new employee recruitment was the need and the resources available based on the concept o the right man on the right job to succeed administrative pre-deconcentration in three Municipio Aileu, Ermera and Liquiça